Guest editorial: Queer theory and criminology - Boukli, Avi (2020)
In 2015, queer theorist Heather Love called for her fellow queer scholars to recognise the centrality of the study of norms and deviance to ‘the intellectual genealogy’ of queer studies. She argued that queer approaches and understandings, with their ‘embrace of a politics of stigma’ and ‘reliance on a general category of social marginality’, were ‘borrowed’ from mid-20th century social science studies of deviance (Love, 2015: 75). For most criminologists, it is axiomatic that this tradition is equally central to our own genealogy, and our concerns with deviance, normativity, social control and the production of power and marginalisation. Despite this shared set of concerns, queer theory and criminology have little contemporary crossover. We share Love’s concern around this state of affairs, but where she is primarily concerned about the stakes for queer studies, the focus of our Special Issue is on what criminologists can gain from greater engagement with the analytic and conceptual tools of queer theory